O‘QUVCHILARNING IJTIMOIY-MADANIY KOMPETENSIYASINI RIVOJLANTIRISHDA BLOG TEXNOLOGIYALARDAN FOYDALANISH YO‘LLARI - Yusupov, B.B. (SCIENCE and SOCIETY, 2024)
The article represents the methodical problem of ways to use blog technologies in the formation of socio-cultural competence of students in the process of literary education.
Keywords: literary education; socio-cultural competence; personality; educational integration; competence; blog technology; turkic folk literature; intellectual ability; technology